The algorithm is ready to be a Shaykh Murabbi: can we define the social media ethics sometime soon? - Paramboor, Jafar (Mission Soft Foundation, 2021)
The algorithmic dilemma that we are in right now is severe than what we really think. It has changed its shape from a smart assistant to an uncontrollable dictator; to an independent troublemaker that can systematically crush one’s everything, and I do not really know what that everything is since everything has now become unpredictable. Even when I type this piece of writing, the algorithm connected to my personal devices, including mobile phone and laptop, are catching up my keywords to give me ‘more accurate’ results in future if I search the social media ethics, for instance. I have observed this phenomenon while making casual conversations with friends through phone, whereby the device starts giving me specific advertisements through my Facebook wall, after ‘carefully’ grasping the exact theme of our conversation; it may be a place to eat, a gadget according to my budget; or anything that I had never imagined at that particular moment. And I do not doubt any more that the algorithm that is engaging with me is going to be a Shaykh Murabbi for myself, being a controller, motivator, and influencer of my consciousness!